• $V = a\cdot b\cdot c$
1 2
$a = \frac{ V}{b\cdot c}$
1 2
$b = \frac{ V}{a\cdot c}$
1 2
$c = \frac{ V}{b\cdot a}$
1 2
$O = 2\cdot (a\cdot b + a\cdot c + b\cdot c)$
1 2
$a = \frac{O-2\cdot b\cdot c}{2\cdot (b+c)}$
1 2
$b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}$
1 2
$c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)}$
1 2
$d = \sqrt{a^{2} +b^{2} +c^{2} }$
1 2
$a = \sqrt{d^{2} -b^{2} -c^{2} }$
1 2
$b = \sqrt{d^{2} -a^{2} -c^{2} }$
1 2
$c = \sqrt{d^{2} -b^{2} -a^{2} }$
1 2

Beispiel Nr: 02
$\text{Gegeben:}\\\text{Höhe} \qquad c \qquad [m] \\ \text{Breite} \qquad b \qquad [m] \\ \text{Volumen} \qquad V \qquad [m^{3}] \\ \\ \text{Gesucht:} \\\text{Länge} \qquad a \qquad [m] \\ \\ a = \frac{ V}{b\cdot c}\\ \textbf{Gegeben:} \\ c=3m \qquad b=2m \qquad V=1m^{3} \qquad \\ \\ \textbf{Rechnung:} \\ a = \frac{ V}{b\cdot c} \\ c=3m\\ b=2m\\ V=1m^{3}\\ a = \frac{ 1m^{3}}{2m\cdot 3m}\\\\a=\frac{1}{6}m \\\\\\ \small \begin{array}{|l|} \hline c=\\ \hline 3 m \\ \hline 30 dm \\ \hline 300 cm \\ \hline 3\cdot 10^{3} mm \\ \hline 3\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline b=\\ \hline 2 m \\ \hline 20 dm \\ \hline 200 cm \\ \hline 2\cdot 10^{3} mm \\ \hline 2\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline V=\\ \hline 1 m^3 \\ \hline 10^{3} dm^3 \\ \hline 10^{6} cm^3 \\ \hline 10^{9} mm^3 \\ \hline 10^{3} l \\ \hline 10 hl \\ \hline \end{array} \small \begin{array}{|l|} \hline a=\\ \hline \frac{1}{6} m \\ \hline 1\frac{2}{3} dm \\ \hline 16\frac{2}{3} cm \\ \hline 166\frac{2}{3} mm \\ \hline 166666\frac{2}{3} \mu m \\ \hline \end{array}$